Effectiveness of nursing education program on nurses knowledge toward Arrhythmia in Kirkuk's teaching hospitals - Hakima S. Hassan; Salah M S. Hassan (Kufa Journal for Nursing Sciences)
Objective: To evaluate the effectiveness of nursing educational program on nurse's knowledge toward arrhythmia in Kirkuk's teaching hospitals.